Be You! - Reynolds, Peter H. (New York, N.Y. : Orchard Books, an imprint of Scholastic, 2020)
The reader is encouraged to "'be your own work of art." To be patient, per sistent, and true. Because there is one, and only one, YOU."--Provided by publisher.
Keywords: Individuality -- Juvenile fiction; Persistence -- Juvenile fiction; Self-esteem -- Juvenile fiction; Individuality -- Fiction; Persistence -- Fiction; Self-esteem -- Fiction